2016
DOI: 10.4049/jimmunol.1600280
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Eculizumab-Mediated Inhibition of the Complement Terminal Pathway

Abstract: Eculizumab is a humanized mAb approved for treatment of patients with paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome. Eculizumab binds complement component C5 and prevents its cleavage by C5 convertases, inhibiting release of both the proinflammatory metabolite C5a and formation of the membrane attack complex via C5b. In this study, we present the crystal structure of the complex between C5 and a Fab fragment with the same sequence as eculizumab at a resolution of 4.2 Å. Five CDRs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 30 publications
10
92
0
Order By: Relevance
“…CFA0322 cross-reacts with cynomolgus monkey C5 and has a highly similar profile to eculizumab in terms of neutralizing activity and binding epitope. Similar to eculizumab 21 , CFA0322 does not bind to C5 R885H, suggesting that binding epitope of eculizumab partially overlaps with that of CFA0322 (data not shown). CFA0322 therefore serves as a surrogate for eculizumab to enable comparison against SKY59.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…CFA0322 cross-reacts with cynomolgus monkey C5 and has a highly similar profile to eculizumab in terms of neutralizing activity and binding epitope. Similar to eculizumab 21 , CFA0322 does not bind to C5 R885H, suggesting that binding epitope of eculizumab partially overlaps with that of CFA0322 (data not shown). CFA0322 therefore serves as a surrogate for eculizumab to enable comparison against SKY59.…”
Section: Resultsmentioning
confidence: 93%
“…recently demonstrated that these patients carry a common single nucleotide polymorphism (SNP) in C5 where arginine at position 885 is substituted with histidine 16 . Since arginine at 885 in the α-chain of C5 is within the binding epitope of eculizumab 11, 21 , this C5 variant cannot be neutralized by eculizumab. In contrast, SKY59 could be expected to neutralize the activity of this C5 variant because the epitope of SKY59 is distinct from that of eculizumab.…”
Section: Resultsmentioning
confidence: 99%
“…Eculizumab forms a 1: 1 complex with C5, and sterically hinders convertases from binding and cleaving C5 into C5a and C5b [74]. Eculizumab successfully prevents intravascular hemolysis and thrombosis and has revolutionized disease management of PNH [75].…”
Section: Eculizumabmentioning
confidence: 99%
“…[6][7][8][9][10] Eculizumab binds C5 with picomolar affinity and inhibits its enzymatic activation by C5 convertases, possibly through steric hindrance. 11,12 However, a recent study indicates that eculizumab not only acts sterically, by blocking binding to the C5 convertase, but also prevents C5 to adopt a primed conformation that is susceptible to processing by the C5 convertase. 13 A similar mechanism has been suggested for the tick inhibitor OmCI (Ornithodoros moubata complement inhibitor) or its recombinant version, coversin, which binds C5 at the face opposite to the eculizumab epitope.…”
Section: Introductionmentioning
confidence: 99%